BIBLIOMETRICS ANALYSIS OF DIGITAL LEADERSHIP RESEARCH - Purwanto, Edi; Irawan, Agustinus Purna (Graduate Program of Universitas Tarumanagara, 2023)
This paper presents a comprehensive analysis of digital leadership research using bibliometric analysis and network visualization techniques. The study utilizes bibliometrics to gain insights and comprehend patterns in scientific publications related to digital leadership. Data from various sources, including articles, conference papers, and book chapters in the Scopus database, was analyzed using mathematical and statistical methods. The search term